Quantifying the Impact of Message Framing on Consumer Attitudes Towards the Consumption of Meat Products in Cape Town: A Consumer Neuroscience Approach - Zunckel, Caitlin (Marketing, 2022)
Is it more effective to evoke negative emotions in social advertisements than positive emotions? This study compared positive and negative message framing strategies in social marketing advertisements that aimed to encourage a reduction in meat consumption. This project explored how each strategy influences consumers' attitudes toward the recommended behaviour and investigated the role of emotional and attentional responses to each message framing strategy. The purpose of this research was to determine whether negatively framed messages are more effective than positively framed messages in influencing consumers' attitudes, emotions, and attention. The motivation of the study was to provide formative research for the design of social marketing interventions to effectively influence consumers' attitudes towards advertised causes with the use of message framing, and to advance theoretical understanding of how consumers respond to social marketing interventions. Furthermore, this research attempted to resolve differences between results obtained in previous framing research in the social marketing context. This study uniquely proposed the use of cutting-edge consumer neuroscience techniques to develop a clearer understanding of consumers' emotional and attentional responses to social marketing advertisements. The results were presented from a mixed-method approach, which combined quantitative and qualitative research methods. An experiment was conducted by using two social marketing print advertisements aimed at encouraging a reduction in meat consumption, by highlighting the impact of consuming meat products on animal welfare. Respondents involved in the experiment viewed an advertisement that was either positively framed or negatively framed. The research applied self-reporting methods, as well as consumer neuroscience methods, including facial coding, galvanic skin response (GSR), and eye-tracking, to explore the proposed research framework. The combination of these methods allowed the collection of data on attitudinal, emotional, and attentional responses. The results of this research demonstrated that negatively framed advertisements are more effective in changing consumers' attitudes towards reducing meat consumption than positively framed advertisements. Thus, messages aimed at encouraging a reduction in consumption should highlight the negative consequences of participating in certain behaviours. Neither emotion nor attention were found to mediate the relationship between message framing and attitude. However, positively framed advertisements elicit significantly higher levels of emotional valence; and negatively framed advertisements elicit significantly higher levels of disgust and attention. Social marketers should, therefore, leverage these feelings of disgust; and they should implement negative framing strategies to increase the attention paid to an advertisement. However, educational social marketing interventions should be considered, in combination with negative message framing, to effectively influence consumers' attitudes towards social issues. These findings have provided research for better developing message framing strategies for the communication of sustainable consumption. Furthermore, these strategies contributed to the existing social marketing literature by addressing the lack of information on marketing efforts aimed at reducing meat consumption. This research also filled important gaps in the literature regarding positive versus negative message framing strategies, and social marketing interventions can now be implemented with an increased understanding of how consumers respond to different message framing strategies.